Analysis of the progress, constraints and challenges of the agrarian program "Sustenta" in Mozambique (Research, Society and Development, 2021)
The Agricultural and Natural Resource Landscape Management Project (Sustenta), whose first phase was launched in 2017 and the second in 2020, is an integrated rural development and poverty alleviation program that aims to improve the quality of life of rural families through the promotion of sustainable agriculture. Since the program was launched in 2017, there has been no participatory evaluation and, above all, with the involvement of local communities and civil society organizations. As well as there are no studies that have already been developed for analyzing the sustainability of the Program. Therefore, this research aimed to analyze the economic sustainability of this program. The study was based on an exploratory study and statistical analysis. In relation to the areas, production and agricultural income registered, it was found that the results obtained did not result in significant increases in production and productivity. The biggest constraints of the program are related to the lack of transparency in the selection of beneficiaries, monitoring and evaluation of the program, the lack of accessible agricultural infrastructure and communication routes in most rural areas and the lack of guarantee of availability of funds for the fulfillment of the program's goals by the year 2024. As a result, the program's sustainability is at risk. In this perspective, the promotion of a participatory evaluation is suggested; the mobilization of resources for the effective fulfillment of the program and greater dissemination of the program.